Music for displaced dyads: a mixed methods feasibility study on the impact of music therapy on the mental health and wellbeing of Ukrainian refugee families - Slabu, Letitia; Coombes, Elizabeth; Mangiacotti, Anthony M. A.; Hadar, Tamar; Franco, Fabia (Frontiers in Psychiatry, 2025)
BackgroundGlobal displacement has reached unprecedented levels, with refugee mothers and children particularly vulnerable to psychological distress. Following the war in Ukraine, many families face trauma, disrupted parenting, and limited access to mental health services. Music therapy (MT) offers a non-pharmacological, culturally adaptable approach to support psychosocial wellbeing. This feasibility study explored the impact of a dyadic MT intervention on Ukrainian refugee caregivers and their children resettled in the UK.MethodsFour groups of 4–6 caregiver-child dyads participated in an 8-week improvisational MT program, co-designed with caregivers and culturally tailored. A mixed-methods approach included: (1) quantitative pre/post measures of PTSD, depression, anxiety, wellbeing, cognitive functioning, parenting self-efficacy, musical home environment, and social connectedness; (2) physiological assessment of respiratory sinus arrhythmia (RSA) as an index of autonomic regulation; and (3) post-intervention semi-structured interviews with caregivers.ResultsSignificant improvements were observed in caregivers’ PTSD, depression, anxiety, and cognitive functioning. RSA data indicated increased parasympathetic activity, suggesting improved emotional regulation. Non-significant trends emerged in parenting and home musical engagement. Qualitative analysis identified enhanced child communication, socio-emotional functioning, and transference of musical engagement into the home.ConclusionThis study is the first to demonstrate the feasibility and potential efficacy of MT for improving mental health and parent-child dynamics among displaced Ukrainian families. Findings support MT as a low-cost, trauma-informed, and scalable intervention. Further research is needed to evaluate its impact in larger, culturally diverse refugee populations through randomized controlled trials.